Effects of Areca catechu Seed and Anredera cordifolia Leaf on Ascaridia galli Infection in the Domestic Chicken (Gallus gallus domesticus) - Prastowo, J.; Herawati, O.; Ariyadi , Bambang; Kurniasih (International Journal of Poultry Science, 2017)
Background and Objective: Ascaridia galli (A. galli) infection can depress the body weight and egg production of domestic chickens. Synthetic anthelmintics are usually used as a treatment but A. galli resistance to synthetic anthelmintics is rising. The aim of this research was to understand the effects of combinations of Areca catechu seed and Anredera cordifolia leaf on the number of eggs per gram (EPG) of feces, body weight, number of Ascaridia galli worms, histopathology and immunoexpression of CD4+lymphocytes in the intestine. Materials and Methods: Three groups of fifteen chickens infected with A. galli were used in this research. For seven days, group 1 was orally administered a combination of 2 mg kg–1 b.wt., of Areca catechu and 1 mg kg–1 b.wt., of Anredera cordifolia, group 2 was given a combination of 5 mg kg–1 b.wt., of Areca catechu and 2.5 mg kg–1 b.wt., of Anredera cordifolia and group 3 was not treated. This research had ethical clearance No. 00040/04/LPPT/IV/2017. On the 10th day, the chickens were euthanized and examined for the number of EPG of feces, body weight, number of A. galli, histopathology and immunoexpression of intestinal CD4+lymphocytes. The data were analyzed statistically and the histopathological changes were analyzed descriptively. Results: The results showed that the combination of Areca catechu and Anredera cordifolia significantly reduced EPG of feces and eliminated A. galli in 60% of the chickens in group 1 but there was no significant difference in body weight among groups. In group 2, the alkaloids and saponins contained in Areca catechu and Anredera cordifolia display antagonistic activity. Thus, high doses do not reduce EPG levels in group 2. Immunohistochemistry showed that wound healing is improved in the treated groups. Conclusion: Ascaridia galli infection might be reduced by a combination of Areca catechu and Anredera cordifolia.